2019
DOI: 10.3389/fncir.2019.00012
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Neural Responses to Cognitive Fatigue in Young and Older Adults

Abstract: Prolonged performance of a demanding cognitive task induces cognitive fatigue. We examined the behavioral and neural responses to fatigue-induced cognitive impairments in young and older adults. Particular emphasis was placed on whether the brain exhibited compensatory neural activity in response to cognitive fatigue. High-density EEG was recorded from a young ( n = 16; 18–33 years of age) and an older ( n = 18; 60–87 years of age) cohort who performed a Stroop tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Haubert and colleagues (2018) observed an increase of N1 amplitudes with time-on-task in individuals performing in a visual attention task. Samuel et al (2019), moreover, found early ERP components to decrease over time, but late ERP components at frontal recording sites to increase. Similarly, Wang et al (2016) observed increases of late ERP amplitudes (640-1,272 ms) at frontal leads during the first 80 min of a 160-min Stroop task experiment.…”
Section: Discussionmentioning
confidence: 91%
“…Haubert and colleagues (2018) observed an increase of N1 amplitudes with time-on-task in individuals performing in a visual attention task. Samuel et al (2019), moreover, found early ERP components to decrease over time, but late ERP components at frontal recording sites to increase. Similarly, Wang et al (2016) observed increases of late ERP amplitudes (640-1,272 ms) at frontal leads during the first 80 min of a 160-min Stroop task experiment.…”
Section: Discussionmentioning
confidence: 91%
“…Aged individuals in comparison to younger adults exhibited a stronger suppressive effect of surround, showing high-contrast suppression when both the center and surround were exposed to the same eye, whereas no such effect was observed when the center and surround were exposed to separate eyes independently [3,93,94]. Hence, it seems that there is a generalized contextual change in surround suppression, contrast, and orientation with normal aging that does not result in a significant decline of performance in aged adults [95]. Even though visual processing is more susceptible to the effects of aging, neural changes in visual circuits related to cognitive tasks do not show a major performance decline in aged individuals as compared to young adults, despite age-related impairment in neural responses of older subjects.…”
Section: Dynamic Balance Of Neuronal Response Properties In Young Andmentioning
confidence: 90%
“…These brain regions mainly subserve cognitive domains such as attention, executive functions, visuospatial functions, episodic memory, language, and number processing [ 80 83 ]. The increased Rs-FC in the dorsal attention RSN could be a compensatory attempt [ 56 ] to preserve these cognitive functions and thus maintain attentional resources in the presence of cognitive fatigue [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%